2019
DOI: 10.1002/cite.201800217
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous H‐ZSM‐5 for the Conversion of Dimethyl Ether to Hydrocarbons

Abstract: The potential of hierarchical H-ZSM-5 zeolites was studied for the conversion of DME to fuel-compatible hydrocarbons. For this purpose, hierarchical H-ZSM-5 zeolites have been prepared from commercial H-ZSM-5 by desilication and organosilane-directed hydrothermal synthesis. The zeolites were characterized by X-ray diffraction, NH 3 -TPD, DRIFTS, and N 2 physisorption measurements. The catalysts have been tested in a tube reactor (1 bar, 648 K). The results indicate important structural changes in framework and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…In the future, options for combining those processes with the chemical utilisation of CO 2 could gain greater relevance, especially if CO 2 conversion can be efficiently linked to H 2 production from electrolysis processes operated with renewable electrical energy [4]. Besides methanol (MeOH), dimethyl ether (DME) is one key intermediate in PtL processes [5,6]. Technically, DME can be produced from syngas in a two-step (indirect) process by the separate dehydration of MeOH or in a one-step (direct) process [7].…”
Section: Introductionmentioning
confidence: 99%
“…In the future, options for combining those processes with the chemical utilisation of CO 2 could gain greater relevance, especially if CO 2 conversion can be efficiently linked to H 2 production from electrolysis processes operated with renewable electrical energy [4]. Besides methanol (MeOH), dimethyl ether (DME) is one key intermediate in PtL processes [5,6]. Technically, DME can be produced from syngas in a two-step (indirect) process by the separate dehydration of MeOH or in a one-step (direct) process [7].…”
Section: Introductionmentioning
confidence: 99%
“…The so-called biosyncrude ® is then transported and fed to a centralized entrained flow gasifier where syngas free of tar is produced [50]. After several gas conditioning steps, the syngas is fed to a direct DME synthesis [51,52], followed by a DTG reactor [53].…”
Section: Methanol and Dimethyl Ether To Gasolinementioning
confidence: 99%
“…An obvious reason for this observation would be its moderate acidity in combination with intraparticle mesoporosity and high crystallinity of the zeolite component (Table , Figure d). This is in line with previous results from our group on powdered hierarchical H-ZSM-5 catalysts for DTG where Z40.05 also showed significantly increased deactivation resistance. , In comparison, the silica-bound counterpart Z40.05-S shows lower DME conversion values that also decline faster when WHSV is increased despite having higher crystallinity and micropore volume (Table , Table S4). An analogous behavior is observed when comparing Z28.05-S with Z28.05-A, although Z28.05-S seems to be more active initially.…”
Section: Catalytic Performancementioning
confidence: 99%
“…Hierarchically structured zeolites have attracted considerable interest as heterogeneous catalysts due to the potential enhancement of catalytic activity and shape selectivity compared to standard microporous zeolites. The current major opinion is that complementary meso- and/or macropores favor mass transport and accessibility of acid sites. For MTH processes, improved conversion in relation to the catalyst volume, increased catalyst lifetime, and enhanced selectivity to gasoline-range products has been observed. For DTG conversion, we have shown that the application of powdered hierarchical H-ZSM-5 catalysts enhanced DME conversion capacity by up to 695% with respect to microporous H-ZSM-5. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation